The students’ extrovert and introvert personality toward speaking performance - Novita Paradilla; Muhammad Zuhri Dj.; Uswatun Hasanah (International Journal of Research on English Teaching and Applied Linguistics, 2021)
This research aims to analyze the influence of personality in speaking performance. The focus was an analysis of the influence of the extrovert and introvert personality of the student toward speaking performance. This research employed a descriptive qualitative research method with a case study approach. The data was collected through questionnaires, interviews, and speaking tests. The subject of this research was students at MA Baytul Mukarromah Welalange. There were 10 consisted of 5 extrovert and 5 introvert students that had been divided by using the Eysenck Personality Questionnaire to acquire the data needed. The data analysis was employed based on the procedure of data analysis suggested by Miles and Huberman that consisted of step reduction, display, and verification data. The result of this data described that there was no influence between extrovert and introvert personality toward speaking performance, but it is influenced by different levels of knowledge and frequent participation or well preparation. It showed that personality types are not a determiner factor for the success of Speaking Performance, it can be suggested that students with different personality types may employ different kinds of strategies for learning. Consequently, whether extrovert or introvert as long as the student had enough knowledge about the topic and also was supported by frequent participation or well preparation, the speaking performance would be better.